Sports-related pain: Exploring the perception of athletes` pain - Wandner, L. D.; Devlin, A. S.; Chrisler, J. C. (Athletic Insight Journal, 2010)
This study was designed to examine the legitimacy of reports of pain by college varsity athletes. The study examined whether pain varied according to factors other than the athletes` description of the pain/injury, including the gender of the athlete and participants, the injury history of the participants, and the sport of the athlete and participants. Participants were 344 Division III female and male varsity athletes. Each participant read one of four vignettes that described an athlete who was in pain and, as a result, had temporarily stopped playing his/her sport. Two of the vignettes described a female athlete, whereas the other two described a male athlete, and two of the vignettes described an individual sport athlete, whereas the other two described a team sport athlete. All other aspects of the vignette were identical. We did not find a gender bias in how the participants perceived the athlete`s pain. However, female participants rated the athlete`s pain higher than the male participants did, and female participants reported taking less time off than the male participants when they themselves were injured. Further, individual sport participants perceived the athlete`s pain to be more legitimate than did team sport participants. Implications for collegiate coaches and trainers are assessed.